2009
DOI: 10.1103/physrevlett.102.047203
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Electromagnon Excitations in MultiferroicRMnO3

Abstract: Electromagnon excitations in multiferroic orthorhombic RMnO3 are shown to result from the Heisenberg coupling between spins despite the fact that the static polarization arises from the much weaker Dzyaloshinskii-Moriya (DM) exchange interaction. We present a model incorporating the structural characteristics of this family of manganites that is confirmed by far infrared transmission data as a function of temperature and magnetic field and inelastic neutron scattering results. A deep connection is found betwee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
111
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(118 citation statements)
references
References 21 publications
5
111
2
Order By: Relevance
“…The strength DE ¼ 0.075 of this electromagnon is weaker than the E o 8a electromagnons reported in TbMnO 3 (DE ¼ 2), thought to arise from the Heisenberg exchange mechanism 14 , and comparable to that assigned to an eigenmode of the spin cycloid (DE ¼ 0.05) 12 . Previously, the application of an optical sum rule has shown that electromagnons in RMn 2 O 5 account for step-like changes in the static dielectric constant 9 .…”
Section: Roommentioning
confidence: 71%
See 1 more Smart Citation
“…The strength DE ¼ 0.075 of this electromagnon is weaker than the E o 8a electromagnons reported in TbMnO 3 (DE ¼ 2), thought to arise from the Heisenberg exchange mechanism 14 , and comparable to that assigned to an eigenmode of the spin cycloid (DE ¼ 0.05) 12 . Previously, the application of an optical sum rule has shown that electromagnons in RMn 2 O 5 account for step-like changes in the static dielectric constant 9 .…”
Section: Roommentioning
confidence: 71%
“…Magnetoelectric coupling creates a new quasiparticle excitation-the electromagnon-at terahertz (THz) frequencies [7][8][9][10][11][12][13] . Electromagnons have been discovered in rareearth-doped compounds such as RMnO 3 and RMn 2 O 5 at low temperature (o70 K), and are thought to result from modifications of the Heisenberg exchange interaction 14,15 , which has a S i Á S j term in the spin Hamiltonian. Single-ion anisotropy (SIA) and biquadratic exchange (BE) are required to capture fully the spectral features of electromagnons in the THz range 16 .…”
mentioning
confidence: 99%
“…In antiferromagnets, magnon resonance frequencies and dispersion are determined by the strength of the antiferromagnetic exchange and by magnetic anisotropy 18 . In multiferroic manganites, far-infrared spectroscopic studies of magnetic excitations helped unravel the underlying microscopic ME interactions that were found to mix magnons with phonons 19,20 . In this article, we present a terahertz (THz) spectroscopic study of long-wavelength magnetic excitations in BFO.…”
Section: Pacs Numbersmentioning
confidence: 99%
“…Detailed investigations of spin excitations in high magnetic field provide the experimental basis for the construction of accurate microscopic magnetic Hamiltonians [7][8][9][10] . THz spectroscopy has also provided the observations of electromagnons [11][12][13][14][15][16][17][18] which are electric-dipole-active spin excitations that receive their electric-dipole activity via microscopic magnetoelectric interactions.…”
Section: Introductionmentioning
confidence: 99%
“…In multiferroic manganites RMnO 3 , THz-frequency electromagnons provided a detailed microscopic mechanism for exchange striction that governs the dynamic magnetoelectricity in these materials 14 . THz optical properties of undoped CBCO have been previously reported by Bordács et al 19 , who found sharp absorption lines in the 1-2 THz range due to spin and optical phonon excitations.…”
Section: Introductionmentioning
confidence: 99%